Effects of Bacillus Calmette-Guérin (BCG Moscow) vaccination on white blood cell count: results of a randomized clinical trial - Cardoso, Amanda da Rocha Oliveira; Conte, Marcus Barreto; Anjos, Laura Raniere Borges dos; Junqueira-Kipnis, Ana Paula; Rabahi, Marcelo Fouad (ABCS Health Sciences, 2025)
Introduction: Bacillus Calmette-Guérin (BCG) vaccination induces innate and specific responses that protect against some severe forms of tuberculosis and have nonspecific effects against other infections. Objective: To evaluate whether revaccination with BCG Moscow is associated with serum increase in total and differential leukocytes. Methods: We conducted an analytical study on the white blood cell count of 156 participants (BCG revaccination group: 80; Control group: 76) of a randomized clinical trial investigating BCG revaccination for the prevention or reduction of complications associated with COVID-19. Blood samples were collected before randomization and after 15 days of intervention. Values were expressed as mean (μ) and standard deviation, using paired t-tests and Student's t-test. Results: BCG revaccination did not alter leukocyte levels between revaccinated (μ, 6019.74±1865.33) and non-revaccinated groups (μ, 6278.75±1823.87), p=0.94. Stratification by sex, obesity, and age did not significantly affect white blood cell levels. Conclusion: Revaccination with BCG Moscow did not stimulate leukocyte production.